(untitled) (International Journal of Food and Nutritional Sciences, 2019)
In our rapidly evolving world, preserving historic buildings and places is paramount to maintaining cultural identity. This study explores the vital role of architectural preservation in ensuring that the character and significance of these sites endure for future generations. Recognizing that "every place has its character and importance," the research emphasizes the urgency of action